Evaluation of the optimal true-ileal-digestible lysine and threonine requirement for nursery pigs - N A Lenehan; J L Usry; C W Hastad; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
A total of 1800 pigs (Exp 1, 360; Exp. 2, 1440) were used in two experiments to evaluate the true ileal digestible (TID) lysine and threonine requirement for 24- to 44-lb pigs. In Exp. 1, there were eight pens per treatment, with five pigs (Genetiporc, initially 23.6 lb and 34 d of age) per pen. Experiment 1 was conducted as a combination of two separate trials to simultaneously examine both the TID lysine and threonine requirement, and hence, determine the appropriate threonine-to-lysine ratio. The first part of the trial consisted of five treatments formulated to contain 0.9, 1.0, 1.1, 1.2, or 1.3% TID lysine, with TID threonine at 66% of lysine. The second part consisted of five treatments formulated to 1.3% TID lysine with increasing TID threonine (0.60, 0.66, 0.73, 0.79, or 0.85%). Other amino acids were formulated to either meet or exceed requirement estimates, thereby ensuring lysine and threonine were first limiting. The highest concentrations of both lysine and threonine (1.3% and 0.85%, respectively) were combined in a single diet, which was used in both trials, to give a total of 10 treatments. From d 0 to 17, ADG and feed efficiency (F/G) improved as TID lysine (quadratic, P<0.02) and threonine (ADG, linear, P<0.03; F/G, quadratic, P<0.04) increased. Regression analysis showed that 95% or more of the maximum response was obtained at a TID threonine-to-lysine ratio of approximately 64% for ADG and 66% for F/G. In Exp. 2, there were 48 pigs per experimental unit (2 pens sharing a fenceline feeder) and six replications per treatment. Pigs (PIC, 24 lb and 39 d of age) were fed experimental diets containing 1.1% TID lysine (calculated to be less than their requirement estimate), with added Lthreonine to give TID threonine concentrations of 0.55, 0.60, 0.66, 0.72, or 0.77% and TID threonine-to-lysine ratios of 50, 55, 60, 65, and 70%. For the 21-d trial, ADG (quadratic, P<0.07) and F/G (quadratic, P<0.01) improved with increasing TID threonine. The best ADG and F/G were observed at 0.72% TID threonine. Hence, it seems that pigs weighing between 22 and 44 lb require approximately 0.72% TID threonine (0.81% total threonine) when fed 1.1% TID lysine, which corresponds to a TID threonine-tolysine ratio of 65%, similar to results in Exp. 1. Data from these two studies indicate an optimal TID threonine-to-lysine ratio of approximately 64 to 66% for 24- to 44-lb pigs.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Lysine; Nursery pigs; Pigs; Threonine; Swine